2012
DOI: 10.4238/2012.august.31.10
|View full text |Cite
|
Sign up to set email alerts
|

11β-hydroxysteroid dehydrogenase type 1 gene expression is increased in ascending aorta tissue of metabolic syndrome patients with coronary artery disease

Abstract: ABSTRACT. 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD-1) 3123©FUNPEC-RP www.funpecrp.com.br Genetics and Molecular Research 11 (3): 3122-3132 (2012) 11β-HSD-1 expressed in ascending aorta of MS patient with CAD activity and mRNA levels are increased in visceral and subcutaneous adipose tissues of metabolic syndrome subjects. We analyzed 11β-HSD-1 expression in human epicardial adipose (EA) and ascending aorta (AA) tissues of metabolic syndrome patients and examined their contribution to the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…In addition to the vasculature, 11␤-HSD1 is also expressed in macrophages (see Section X.B.). Little is known about the role of 11␤-HSD1 in atherosclerosis; however, a recent study demonstrated increased expression in the ascending aorta of patients with metabolic syndrome-associated coronary artery disease (178).…”
Section: B 11␤-hsd1 In the Vascular Systemmentioning
confidence: 99%
“…In addition to the vasculature, 11␤-HSD1 is also expressed in macrophages (see Section X.B.). Little is known about the role of 11␤-HSD1 in atherosclerosis; however, a recent study demonstrated increased expression in the ascending aorta of patients with metabolic syndrome-associated coronary artery disease (178).…”
Section: B 11␤-hsd1 In the Vascular Systemmentioning
confidence: 99%
“…Deficiency in, or inhibition of, 11β-HSD1 exacerbates acute inflammation although it is protective against the low-grade chronic inflammation associated with metabolic and cardiovascular disease [2,3]. 11β-HSD1 expression is increased at sites of inflammation, including in arthritis [4,5], obesity [6,7] and atherosclerosis [8], possibly mediated by the pro-inflammatory cytokines, IL-1α/β and TNFα, which increase levels of mRNA encoding 11β-HSD1 in a variety of cells [2]. The HSD11B1 gene encoding 11β-HSD1 is transcribed from two different promoters, P1 and P2, which by RNA splicing produce the same protein [9].…”
Section: Introductionmentioning
confidence: 99%
“…Mediastinal adipose tissue 11β (Beta)-HSD1 has been linked with coronary atherosclerosis [ 92 ]. The same authors demonstrated increased 11β (Beta)-HSD1 expression in aortas of obese patients with the metabolic syndrome [ 93 ]. 11β (Beta)-HSD1 inhibition in apoE knockout mice achieved signifi cant reduction atherosclerotic load suggesting a role in plaque formation [ 94 ].…”
Section: Cardiovascular Systemmentioning
confidence: 74%